Comparison of kinanthropometric profiles of elite turkish taekwondo players with or without medals in european championships - AGOPYAN, ANİ; KÜÇÜK YETGİN, MERAL; RAMAZANOĞLU, NUSRET; CUMBUR, CANSEL (My University, 2022)
This study aims to determine the possible differences anthropometric characteristics and body composition profiles of elite taekwondo players with or without medals in European championships. Twenty-one black-belt elite taekwondo athletes (17.4 +/- 1.2 years) from the Turkish national team were divided into two groups, namely, medalists (MEC; n =11) and non-medalists (NmEC; n=10) in European championships. Twenty-eight anthropometric measurements including height, body mass, length, circumferences, breadth, and skinfolds were taken following the standard techniques proposed by the International Society for the Advancement of Kinanthropometry (ISAK). Body composition variables were evaluated by using skinfold thickness measurements. Results demonstrated that anthropometric and body composition, variables did not differ significantly between medalist and non-medalist taekwondo players (p>0.01). Our athletes have a low percentage of body fat and high muscle mass profile. Medalist and non-medalist elite Turkish taekwondo players in the European championships do not differ in terms of anthropometric and body composition components. They have a similar body composition profile suitable for taekwondo players and within acceptable healthy ranges. The present study assists coaches in the formulation of appropriate training programs aiming the development for managing the body composition status of players, which will be associated with high-level performance in taekwondo. Future studies should include body composition and somatotype profile inspection throughout the weight categories.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Anatomi; Biyokimya; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Fundamental Medical Sciences; Human Anatomy; Biochemistry; Life Sciences; Natural Sciences; ANATOMİ VE MORFOLOJİ; Biyoloji ve Biyokimya; Yaşam Bilimleri (LIFE); ANATOMY & MORPHOLOGY; BIOLOGY & BIOCHEMISTRY; Life Sciences (LIFE); Biochemistry (medical); Anatomy; Anthropometry; Body composition; Taekwondo; INDICATORS; INDEXES; Anthropometry; Body composition; Taekwondo